The effects of forest burning and logging toward regeneration ability of Sowang (Xanthostemon novaguineense Valet.) in Cycloop Mountain, Jayapura, Papua - SRI WILUJENG (Biodiversitas Journal of Biological Diversity, 2010)
Wilujeng S (2010) The effects of forest burning and logging toward regeneration ability of Sowang (Xanthostemon novaguineense Valet.) in Cycloop Mountain, Jayapura, Papua. Biodiversitas 11: 194-199. Sowang (Xanthostemon novaguineense Valet.) is an endemic plant of New Guinea Island, which is threatened by human activities through land conversion, forest burning and logging. This research aims to know the Sowang developmental phase and stem branching, seedling dominance level, and effect of environmental factor alteration towards the amount of Sowang seedlings at burning and logging areas, and natural forest as control parameters. Sowang stem, derived from shoot of burning area, grows branchy from the lower part of stem. Sowang stem derived from seed grows monopodially. Sowang seedling, derived from stem shoot of burning area, have already started flowering phase that occurs all seasons. Individual of Sowang, derived from seed of logging area and natural forest, flowers on the tree level once a year. Sowang seedling became dominant species at burning area. Environmental factors affect Sowang seedling population density were crown covering and light intensity.Key words: population, Sowang, Xanthostemon novaguineense, branching, flowering, domination